The franchise relationship in China: agency and institutional theory perspectives. Issue 9 (19th August 2014) - Doherty, Anne Marie; Chen, Xiaomin; Alexander, Nicholas
Abstract : Purpose: Explores the franchise relationship in China, focusing on the relational constructs of power, control, support and conflict in this developing franchise environment. Agency theory has dominated franchise research. A more rounded theoretical interpretation of the franchising relationship is offered by employing both agency theory and institutional theory perspectives. Design/methodology/approach: Adopts an interpretive approach, employing in-depth interviews with franchisors and franchisees in nine franchise organisations operating in the retail sector in China. Contributes a fuller understanding of how to manage the research process in China. Findings: Reveals how the relational constructs of power, control, support and conflict are manifest in the franchise relationship in China. The explanatory power of agency theory is apparent when viewed in terms of the vertical agency problem. However, free riding outside the franchise system, in the form of counterfeiting, mitigates against the occurrence of free riding within it. With regard to institutional theory, we demonstrate that the regulatory institutional pillar is a crucial foundation for the franchise relationship. Practical implications: Offers insights for franchisors and franchisees considering franchise relationships in China. Originality/value: For the first time in the literature, we offer insights into key elements of the franchise relationship in China. Employing both agency theory and institutional theory facilitates a rounded explanation of the developing franchise environment in China.